RARE-53. THE ROLE OF RADIATION AND CHEMOTHERAPY IN ADULT PATIENTS WITH HIGH-GRADE BRAINSTEM GLIOMAS. (11th November 2019) - Kerezoudis, Panagiotis; Lu, Victor; Alvi, Mohammed; Goyal, Anshit; Bydon, Mohamad; Kizilbash, Sani; Burns, Terry
Abstract: BACKGROUND: High-grade gliomas (HGGs) of the brainstem represent a rarer subtype of central nervous system tumors compared to their supratentorial counterpart. Predictors of survival and patterns of care have not yet been established on a national, multi-institutional scale. METHODS: The National Cancer Database was queried for adult cases surgically diagnosed with brainstem high-grade glioma. An array of patient demographics, comorbidities, tumor characteristics and treatment parameters were captured. Predictors of survival were investigated using multivariable Cox proportional hazards regression analysis adjusting for age, insurance status, Charlson comorbidity score, tumor grade, tumor size and type of treatment. RESULTS: A total of 422 patients (median 51 years, 60% males) were analyzed. Two hundred eighty one received postoperative radiation with chemotherapy (66.6%), thirty-nine had radiation alone (9.2%), while the remaining had no adjuvant treatment (24.2%). Median radiation dosage was 54Gy. Overall median survival was 9.8 months (95% CI 8.8–12). Survival was significantly longer (p< .001) in the chemotherapy+radiation group (median: 14.2 months, 95% CI 11.7–17.1) compared to radiation alone (median: 5.7 months, 95% CI 3.7–12) and no adjuvant treatment (median:1.8 months, 95% CI 1.4–4). In multivariable analysis, increasing age (HR 1.87, 95% CI 1.47–2.37, p< .001) was associated with worse survival, whereas radiation with chemotherapy (HR 0.67, 95% CI 0.46–0.98, p=0.038) were associated with lower hazards of death compared to radiation alone. In subgroup analysis, the effect of adjuvant chemotherapy with radiation remained significant for grade IV (HR 0.46, 95% CI 0.28–0.76, p=0.003), but not for grade III tumors (HR 0.87, 95% CI 0.48–1.58, p=0.65). CONCLUSION: Findings of the present analysis demonstrate the effectiveness of radiation with chemotherapy for adult patients with high-grade brainstem gliomas, particularly grade IV. Further research should aim on identifying specific patient profiles and molecular subgroups that are more likely to benefit from multimodality therapy.